Physiological and pathological phosphorylation of tau by Cdk5 - Kimura, Taeko; Ishiguro, Koichi; Hisanaga, Shin-ichi (Frontiers in Molecular Neuroscience, 2014)
Hyperphosphorylation of microtubule-associated protein tau is one of the major pathological events in Alzheimer’s disease (AD) and other related neurodegenerative diseases, including frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17). Mutations in the tau gene MAPT are a cause of FTDP-17, and the mutated tau proteins are hyperphosphorylated in patient brains. Thus, it is important to determine the molecular mechanism of hyperphosphorylation of tau to understand the pathology of these diseases collectively called tauopathy. Tau is phosphorylated at many sites via several protein kinases, and a characteristic is phosphorylation at Ser/Thr residues in Ser/Thr-Pro sequences, which are targeted by proline-directed protein kinases such as ERK, GSK3β, and Cdk5. Among these kinases, Cdk5 is particularly interesting because it could be abnormally activated in AD. Cdk5 is a member of the cyclin-dependent kinases (Cdks), but in contrast to the major Cdks, which promote cell cycle progression in proliferating cells, Cdk5 is activated in post-mitotic neurons via the neuron-specific activator p35. Cdk5-p35 plays a critical role in brain development and physiological synaptic activity. In contrast, in disease brains, Cdk5 is thought to be hyperactivated by p25, which is the N-terminal truncated form of p35 and is generated by cleavage with calpain. Several reports have indicated that tau is hyperphosphorylated by Cdk5-p25. However, normal and abnormal phosphorylation of tau by Cdk5 is still not completely understood. In this article, we summarize the physiological and pathological phosphorylation of tau via Cdk5.